Analisis Work of Balance dan Budaya Organisasi terhadap Employee Engagement dalam Perspektif Bisnis Islam (Studi Pada J&T Express Way Kandis) - Chandra Setiawan; ChandraSetiawan; Suhendar; Verawati, Heni (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study examines the influence of work-life balance and organizational culture on employee engagement from an Islamic business perspective at J&T Express Way Kandis. Although employee engagement has been widely researched, most previous studies have focused on the banking, education, and MSME industries, and have not integrated Islamic values ​​in the measurement of organizational variables. This condition indicates a research gap related to the lack of empirical evidence on how Islamic principles influence engagement in the modern logistics industry, especially in expedition companies facing high operational pressure. Starting from this gap, this study offers a novelty through an exploratory quantitative approach that integrates the values ​​of tawazun, akhlakul karimah, and maslahah in the analysis of work-life balance, as well as shiddiq, amanah, tabligh, and fathonah in the study of organizational culture. Data were collected from 75 employees using a 5-point Likert scale questionnaire and analyzed using multiple linear regression. The results show that work-life balance (t = 4.736; p < 0.05) and Islamic organizational culture (t = 4.623; p < 0.05) significantly influence employee engagement, with a simultaneous contribution of 61.8% (F = 58.347; p < 0.05). This finding confirms that the application of Islamic values ​​not only serves as a moral guideline but also has a measurable impact on increasing engagement in the logistics sector, which is also a new contribution to strengthening the literature on Islamic value-based HRM in the contemporary industrial environment.